2017
DOI: 10.21608/eajbse.2017.14468
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Larval Secretions of the Blowfly, Lucilia sericata (Diptera: Calliphoridae)

Abstract: Journal of Medical Entomology and Parasitology is one of the series issued quarterly by the Egyptian Academic Journal of Biological Sciences. It is an important specialist journal covering the latest advances in that subject. It publishes original research and review papers on all aspects of basic and applied medical entomology, parasitology and host-parasite relationships, including the latest discoveries in parasite biochemistry, molecular biology, genetics, ecology and epidemiology in the content of the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, focus on new strategies for the eradication of severe infections associated with biofilm is very important. The presence of small antibacterial agents (1 kDa) in E/S showed that against a range of bacteria including S. aureus is active (Elshehaby et al 2017). E/S enzymes can dissolve biofilms and inhibit biofilm growth (Elshehaby et al 2017;Harris et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, focus on new strategies for the eradication of severe infections associated with biofilm is very important. The presence of small antibacterial agents (1 kDa) in E/S showed that against a range of bacteria including S. aureus is active (Elshehaby et al 2017). E/S enzymes can dissolve biofilms and inhibit biofilm growth (Elshehaby et al 2017;Harris et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the preference of the mode of action, larvae of L. sericata initiate their activities in the wound by chemical secretions and excretions (Nigam et al 2006;Sherman 2014). Maggot extractions and secretion (ES) treatment have been shown to aid the healing process by stimulates the regeneration of blood vessels and also has a proliferative effect on the growth of human endothelial cells (Elshehaby et al 2017). Many studies have shown evidence that larvae have antimicrobial activity in two ways, including antimicrobial action by ingestion larvae of wound bacteria, which are killed when they enter the larval 12 digestive tract also through the antimicrobial activity of secretions and larval excretions, including salivary gland secretions and fecal wastes (Valachova et al 2013).…”
Section: Introductionmentioning
confidence: 99%